The Influence of LCM Number Board Media on Elementary School Students' Cognitive Mathematics Learning Outcomes - Rosita Damayanti; Muhammad Abduh (FKIP - Universitas Riau, 2026)
This study aims to determine the effect of using the Least Common Multiple (LCM) Number Board media on elementary school students’ cognitive learning outcomes in mathematics. The study employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The participants consisted of an experimental class and a control class. Data were collected through pretests and posttests to measure students’ cognitive learning outcomes. The experimental class was taught using the LCM Number Board media, while the control class received conventional instruction. The results showed that the use of the LCM Number Board media significantly improved students’ mathematics learning outcomes. The average score of the experimental class increased from 60.73 on the pretest to 88.07 on the posttest, which was higher than the improvement achieved by the control class. These findings indicate that concrete learning media can help students understand abstract mathematical concepts more effectively and enhance their cognitive achievement in mathematics learning. Therefore, the LCM Number Board media can be used as an alternative instructional medium to support mathematics learning in elementary schools.